Penanggulangan Pekerja Anak Dibawah Umur Di Persimpangan Jalan Berdasarkan Undang-Undang Nomor 35 Tahun 2014 Tentang Perlindungan Anak di Kota Pekanbaru - Olivia Anggie Johar*; Muhammad Yusuf Daeng; Tri Novita Sari Manihuruk (Jurnal Karya Ilmiah Multidisiplin (JURKIM), 2023)
The handling of underage child labor in Pekanbaru City must be carried out immediately because considering that there are still many children who are exploited to be employed at the existing intersections in Pekanbaru. Pekanabaru City Government in dealing with underage child labor in the city of Pekanbaru has carried out its roles and duties, but it has not been maximized. The inhibiting factor is the lack of attention from parents to children who are victims of exploitation, there is no deterrent effect experienced by parents of children and children who are victims of exploitation, there are persons who take personal advantage by exploiting children. Efforts made by the Pekanbaru city government are that abandoned children or children who do not have parents will be placed in orphanages, children who have parents will be returned to their parents, the Pekanbaru city government will provide guidance to children, the Pekanbaru city government will provide training. against children, provide economic assistance to children, provide legal action or convict people who exploit children for personal gain. The method used in this study is sociological legal research with research locations in the city of Pekanbaru